2001
DOI: 10.1128/jcm.39.7.2531-2540.2001
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Rifampin-Resistant Mycobacterium tuberculosis Strains by Hybridization, PCR, and Ligase Detection Reaction on Oligonucleotide Microchips

Abstract: Three new molecular approaches were developed to identify drug-resistant strains of Mycobacterium tuberculosis using biochips with oligonucleotides immobilized in polyacrylamide gel pads. These approaches are significantly faster than traditional bacteriological methods. All three approaches-hybridization, PCR, and ligase detection reaction-were designed to analyze an 81-bp fragment of the gene rpoB encoding the ␤-subunit of RNA polymerase, where most known mutations of rifampin resistance are located. The cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
89
0
4

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 123 publications
(96 citation statements)
references
References 32 publications
3
89
0
4
Order By: Relevance
“…Microarrays allow several thousands of captured nucleic acid probes to be spotted on a small surface on a solid support, generally a glass slide (1)(2)(3)(4). Efforts have been undertaken to adapt the microarray technology for rapid identification of biomolecules by means of signal transduction after binding to specific probes attached to a solid support (5)(6)(7)(8)(9)(10). Per se, there is a need for a rapid (less than 1 h) and sensitive microarray system suitable for the molecular diagnosis of infectious diseases, which involves the detection of a wide variety of microbial pathogens as well as associated virulence genes such as antimicrobial resistance genes or toxin genes (11,12 ).…”
mentioning
confidence: 99%
“…Microarrays allow several thousands of captured nucleic acid probes to be spotted on a small surface on a solid support, generally a glass slide (1)(2)(3)(4). Efforts have been undertaken to adapt the microarray technology for rapid identification of biomolecules by means of signal transduction after binding to specific probes attached to a solid support (5)(6)(7)(8)(9)(10). Per se, there is a need for a rapid (less than 1 h) and sensitive microarray system suitable for the molecular diagnosis of infectious diseases, which involves the detection of a wide variety of microbial pathogens as well as associated virulence genes such as antimicrobial resistance genes or toxin genes (11,12 ).…”
mentioning
confidence: 99%
“…Oligonucleotide based DNA arrays have been used for parallel species identification and rifampin resistancerelated mutations in mycobacteria (Troesch et al, 1999) and, more specifically, for the detection of M. tuberculosis strains that are resistant to rifampin (Yue et al, 2004) or isoniazid, kanamycin, streptomycin, pyrazinamide, and ethambutol (Gegia et al, 2008). Oligonucleotide microarrays were developed to analyze and identify drugresistant M. tuberculosis strains, and it was found that the results were comparable with those of standard antimicrobial susceptibility testing (Strizhkov et al, 2000;Mikhailovich et al, 2001). A low-cost and -density DNA microarray was designed to detect mutations that confer isoniazid and rifampin resistance in M. tuberculosis isolates.…”
Section: Gene Expression Profiles Of Drugs Resistance Inhibitors Anmentioning
confidence: 99%
“…Jalava and Marttila [91] described that high-density oligonucleotide arrays may also offer a powerful solution to genotypic detection of drug-resistant MTB isolates. So far, these microarrays have mainly been used for the detection of rifampin resistance [72,123,198] with promising results. Consequently, Jalava and Marttila [91] argue that the DNA microarray strategy could be expanded to include parallel testing of various genes mediating drug resistance in MTB.…”
Section: Promising New Technologiesmentioning
confidence: 99%
“…This method can discriminate single-base differences. On-chip ligase detection reaction is applied to identify approximately 1% of mutant sequences in model samples consisting of mixtures of DNA from wild-type and resistant strains (see [123] for details).These technologies may be useful for clinical research in developed countries, but remain inaccessible for a TB control program on a large scale including low-resource countries.…”
Section: Promising New Technologiesmentioning
confidence: 99%
See 1 more Smart Citation